2015
DOI: 10.1038/leu.2015.291
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT focal, but not osteolytic, lesions predict the progression of smoldering myeloma to active disease

Abstract: Identification of patient sub-groups with smoldering multiple myeloma (SMM) at high risk of progression to active disease (MM) is an important goal. 18F-FDG PET/CT (positron emission tomography (PET) integrated with computed tomography (PET/CT) using glucose labelled with the positron-emitting radionuclide (18)F) allows for assessing early skeletal involvement. Identification of osteolytic lesions by this technique has recently been incorporated into the updated International Myeloma Working Group criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 36 publications
2
98
0
3
Order By: Relevance
“…Standardization is also required for the use and implication of positron emission tomography (PET)/computed tomography (CT). In their study on 120 patients with SMM, the Bologna group reported that PET/CT identified either focal lesions or a diffuse infiltration in 19 (16%) patients [23]. Patients presenting small osteolytic lesions were excluded from the study.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Standardization is also required for the use and implication of positron emission tomography (PET)/computed tomography (CT). In their study on 120 patients with SMM, the Bologna group reported that PET/CT identified either focal lesions or a diffuse infiltration in 19 (16%) patients [23]. Patients presenting small osteolytic lesions were excluded from the study.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Risk of progression to symptomatic MM within 2 years was 58-61% [57,58]. Risk progression in light-chain SMM is approximately 5% per year during the first 5 years and decreases thereafter [23].…”
Section: % Of Totalmentioning
confidence: 96%
“…Risk of progression at 7 years (%) hypermetabolism without underlying osteolysis on PET-CT (8-16% of the patients with SMM) have a higher probability of progression, compared to patients without these abnormalities [57,58]. Risk of progression to symptomatic MM within 2 years was 58-61% [57,58].…”
Section: % Of Totalmentioning
confidence: 99%
“…Kornélia Kajȧry and Dr. Zsuzsa Molnár publish their research article entitled "The role of 18F-FDG PET/CT before and after the treatment of multiple myeloma: Our clinical experience" in this issue of AMOR (page [20][21][22][23][24][25][26][27][28][29][30] ung cancer is responsible for millions of death worldwide each year and it is the second most common cancer in both men and women. According to the American Cancer Society, lung cancer is responsible for about 1 in 4 cancer deaths and 14% of all new cases.…”
Section: Dr Kajȧry With a Patient (Photo Credits: Dr Kornélia Kajȧry)mentioning
confidence: 99%